Risk Factors and Pharmacological Interventions Impacting Cerebrovascular Ischemic Events in Giant Cell Arteritis: A Narrative Review - Muhammad Osama Siddiqui; Mohammad Ali Syed; Ayaan Ahmed Qureshi; Mustafa Hussain Imam; Jatin Motwani; Verkha Kumari; Arooba Siddiqui; Noor Ul Ain; Mohammed Hammad Jaber (Immunity, Inflammation and Disease)
ABSTRACT Introduction Giant cell arteritis (GCA) is a common vasculitis predominantly affecting larger vessels, especially in individuals aged 70–79. Cerebrovascular ischemic events (CIE), such as stroke and transient ischemic attacks, are serious but rare complications of GCA, with a pooled prevalence of 4%. Some studies found that within 2 weeks of GCA diagnosis, 74% and 34% of patients experience transient or severe ischemic events, respectively. Aims Our study aims to help physicians better manage GCA patients to reduce GCA‐related CIE by indicating important risk factors and pharmacological intervention to prevent GCA‐related CIE, particularly in the first few days of diagnosis when the risk of CIE is highest. Methods A comprehensive literature search was conducted using Pubmed, Google Scholar, Scopus, and other relevant medical databases. As this study was a narrative review, the literature search was done in a nonsystematic manner. Studies published from 2000 to 2024 were reviewed in a nonsystematic manner for information on incidence, pathology, risk factors, pharmacological intervention, and management of GCA‐related CIE. Results Findings indicate that age, male gender, hypertension, and smoking significantly increase the risk of GCA‐related CIE, while factors such as anemia, higher body mass index (BMI), and elevated inflammatory markers (C‐reactive protein [CRP] and erythrocyte sedimentation rate [ESR]) appear to have protective effects. Symptoms of ischemia in the ophthalmic artery were identified as the strongest predictors of CIE. Pharmacological treatments, including glucocorticoids and tocilizumab, are instrumental in managing and potentially preventing CIE in GCA patients, with adjunctive therapies such as aspirin and antiplatelet agents also showing promise. Conclusion GCA‐related CIE such as stroke can be very debilitating and deadly conditions, particularly when GCA is initially diagnosed. However, with early diagnosis and proper management of risk factors, GCA‐related CIE can be prevented and its severity can be reduced. Ischemia in the ophthalmic artery is found to strongly predict GCA‐related CIE while aspirin and antiplatelet agent during the first 3 months may prevent GCA‐related CIE. Risk factors such as BMI and smoking may help in stratifying the risk of GCA‐related CIE. This review underscores the importance of further studies with detailed, well‐designed approaches to risk factor analysis to strengthen these associations. Identifying these risk factors is crucial for reducing morbidity and mortality, equipping physicians to better assess and mitigate the risk of CIE in GCA patients.